Biopolymer-based functional composites for medical applications - Park, Sung-Bin; Lih, Eugene; Park, Kwang-Sook; Joung, Yoon Ki; Han, Dong Keun (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Over the last decade, numerous biopolymers have received more attention in medical applications involving novel biomaterials because of their biocompatibility, biodegradability, and ease of processing. To date, many biopolymer-based functional composites have been developed to increase the value of raw biopolymers obtained from natural sources or microbial systems. This review article covers general information on various biopolymers, important methods for biopolymer-based composites preparation including their advantages and disadvantages, and surface topography for tissue engineering. In addition, this article provides comprehensive knowledge and highlights recent research on functional biopolymer composites used in various medical applications, such as tissue engineering comprising skin, bone, cartilage, vascular graft, and other organs, implantable medical devices including stent and barrier membrane, and some delivery systems of bioactive agents. Furthermore, the article presents a brief overview on several challenges and future scope in this field. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: MESENCHYMAL STEM-CELLS; ELASTIN-LIKE POLYPEPTIDE; TISSUE-ENGINEERING SCAFFOLDS; GROWTH-FACTOR DELIVERY; LONG-TERM MAINTENANCE; FOCAL ADHESION KINASE; HIGH-MOLECULAR-WEIGHT; OSTEOBLAST-LIKE CELLS; IN-VITRO DEGRADATION; GAMMA-GLUTAMIC ACID